Deaf empowerment emergence, struggle, and rhetoric - Jankowski, Katherine A. (Gallaudet Univ. Press, 1997)
The story of "the struggle between the dominant hearing society and Deaf people over the best means of communication, with the educational setting as the constant battleground." Includes the influences of other social movements of the 60s and 70s, the Deaf President Now! protest at Gallaudet University, and suggestions and hopes for the future.--Jacket.